PENERAPAN BLENDED LEARNING BERBANTUAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.5 SMP WIDIATMIKA - I Putu Ade Andre Payadnya; Putu Yulia Prawestri (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
This study aims to improve mathematics learning outcomes of students of class VII.5 SMP Widiatmika. The main topic of the linear equations and inequalities of one variable during mathematics learning through the application of blended learning assisted by instructional videos. There are several factors that affect the learning outcomes of students in grade VII.5 SMP Widiatmika. This research is a Classroom Action Research (CAR) which was conducted in two cycles. Each cycle is carried out for 3 meetings, namely 2 meetings for action parts and 1 meeting to conduct the final cycle test. The test used to collect student learning outcomes is in the form of multiple choice questions consisting of 30 questions. The application of blended learning based on video learning is proven to be successful in improving the mathematics learning outcomes of class VII.5 students of SMP Widiatmika. It can be seen from the average student learning outcomes which have increased from first cycle to the next cycle, the average student learning outcomes in the first cycle is 62,67 with the percentage of completeness is 56%; The average student learning outcomes in cycle II was 80,20 with the percentage of student completeness was 80%